Another Girl, Another Planet. - Greenberg Rohatyn, Jeanne; Homes, A.M. (New York : Lawrence Rubin Greenberg Van Doren Fine Art, 1999)
Becker, Julie ; Brandt, Gabriel ; Dobai, Sarah ; Gage, Jenny ; Grannan, Katy ; Hoey, Dana ; Hanzlová, Jitka ; Jones, Sarah ; Kurland, Justine ; Marder, Malerie ; Post, Liza May ; Singh, Dayanita ; Tandberg, Vibeke
biog., tent., bibliog. p. 29-31
Engels
Another Girl, Another Planet, Lawrence Rubin - Greenberg Van Doren - Fine Art, New York, March 23 - April 17, 1999
boek